Study of seed appearance and germination characteristics of Iranian edible onion (Allium cepa L.) native landraces - Reza Kamaei; Mohammad Kafi; Reza Tavakkol Afshari; Saeid Malekzadeh Shafaroudi; Jafar Nabati (علوم و فناوری بذر ایران, 2022)
In order to identify different landraces of onion seeds in terms of germination characteristics, an experiment was conducted in a completely randomized design with four replications in the Biology Laboratory of the Faculty of Agriculture, Ferdowsi University of Mashhad in 2020. The experimental treatments were 29 native landraces of onion seeds from different regions of Iran and two improved cultivars as control. The results showed a significant difference for all measured indices amongst landraces. Also, the clustering results of the landraces, based on the apparent characteristics, showed that among the 4 clusters, the third cluster, which includes 9 landraces (Harsin, Kavar, Azarshahr, Bonab, Yasuj, Qorveh, Kashan white, Neishabour white and Qoli Qeseh) has better appearance characteristics in terms of 1000-grain weight (average 4.54 g), grain length (average 3.08 mm) and grain diameter (1.9 mm). Also, it was shown based on germination characteristics that among the six indivisual clusters, the fourth cluster with 7 landraces including Yasuj, Kashan white, Dorcheh Yellow, Turkey, Tarom, Neishabour white and Qorveh has better germination characteristics. In general, it can be concluded that based on the appearance and germination characteristics, Yasuj, Kashan white and Neishabour white landraces showed a better seed quality.